Efficacy and Safety of the Traditional Japanese Medicine Keigairengyoto in the Treatment of Acne Vulgaris - Kotaro Ito; Saori Masaki; Manabu Hamada; Tetsuo Tokunaga; Hisashi Kokuba; Kenji Tashiro; Ichiro Yano; Shinichiro Yasumoto; Shinichi Imafuku (Hindawi Limited, 2018)
Several traditional Japanese medicines including Keigairengyoto (KRT) are used to treat acne vulgaris, but there is no robust evidence of their effectiveness. In this study, we examined the effectiveness and safety of KRT in treating acne vulgaris. An open-label, randomized, parallel control group comparison was conducted with a conventional treatment group (adapalene and topical antibiotics; control group) and a KRT group (control treatment plus KRT). The test drugs were administered for 12 weeks to patients (15 to 64 years, outpatient) with inflammatory acne on their face, and the amount of acne at 2, 4, 8, and 12 weeks was measured. Sixty-four patients were enrolled; 29 patients in each group were included in the analysis. Twenty-eight patients in the control group and 24 patients in the KRT group were included in the efficacy analysis. The number of inflammatory skin rashes at 4 and 8 weeks in the KRT group was significantly decreased compared with the control group. There was no significant difference between the two groups in noninflammatory eruptions and general rashes. There were no serious adverse events in both groups. KRT may be a useful agent in patients with inflammatory acne in combination with conventional treatments. This trial is registered with UMIN 000014831.